Direct‐Printing Hydrogel‐Based Platform for Humidity‐Driven Dynamic Full‐Color Printing and Holography. (20th December 2022) - Dai, Chenjie; Li, Zile; Li, Zhe; Shi, Yangyang; Wang, Zejing; Wan, Shuai; Tang, Jiao; Zeng, Yongquan; Li, Zhongyang
Abstract: Hydrogel materials endow the flat optics platform with active tuning capability, owing to their remarkable humidity‐responsive swelling behavior. Despite recent advances in hydrogel‐based devices for spectral tuning, their complex patterning processing and limited functionality obstruct them from practical applications. Herein, a single‐step direct‐printing technique is originally demonstrated with an active hydrogel material platform for realizing unprecedented multi‐field full‐color display dynamics. Through exploring the dose‐induced shrinkage on polyvinyl alcohol, the stepwise hydrogel nanocavities sandwiched by ultrathin metallic films can be directly printed by grayscale e‐beam lithography. Due to the tunable structural coloration from hydrogel nanocavity scaling, multi‐functionalities are successfully created for optical concealment, dynamic coloring, and dynamic full‐color holography. By encoding the cavity‐dependent transmission phase into the direct‐printed hydrogel platform, it originally enables the projected full‐color holographic dynamics in real‐time by simply exhalation, beyond the static holographic display or monochromatic holographic switching. The proposed active displays can rapidly respond to the surrounding humidity change at a millisecond‐level (< 150 ms). Such a direct‐printing strategy for hydrogel nanocavity represents a critical advance toward the unprecedented dynamic full‐color display, and suggests promising applications in optical security, gas sensing, multispectral imaging, full‐color holography, and next‐generation display techniques. Abstract : A hydrogel‐based nanocavity platform using single‐step direct‐printing technology is demonstrated for versatile full‐color display dynamics. By exploiting the dose‐induced shrinkage of polyvinyl alcohol, the stepwise hydrogel nanocavities can be directly printed by grayscale e‐beam lithography. Due to the tunable structural coloration from hydrogel nanocavity scaling, multi‐functionalities are successfully created for optical concealment, dynamic coloring, and dynamic full‐color holography in real‐time.